Pengaruh Model Pembelajaran Problem Based Learning terhadap Kemampuan Menulis Teks Anekdot Siswa Kelas X SMA Negeri 1 Cigemblong - Zaein, Sifa Ma’riffatu (Universitas Mathla'ul Anwar Banten, 2024)
This research was conducted based on the problem of the low skills in writing anecdotal texts among high school students, especially in terms of analyzing and compiling social phenomena into critical and humorous anecdotal texts. This research aims to determine the difference in the effect of writing skills on students who learn using the Problem Based Learning (PBL) model and students who use the Discovery Learning learning model. The method in this research uses a quantitative approach. The population and sample in this research were class The instrument used in this research was anecdotal text writing skills test. The test used is a written test. Based on the results of data analysis, it was concluded that there was a difference in the influence of anecdotal text writing skills between students who studied using the Problem Based Learning model and students who studied using the Discovery Learning model. The anecdotal text writing skills of students who learn using the Problem Based Learning model are better than students who learn using the Discovery Learning model. This can be seen from the results of hypothesis testing using the t-test, which shows significant results. Therefore, it can be stated that there is a significant difference in improvement in the anecdotal text writing skills of high school students who are taught using the Problem Based Learning (PBL) model.